Evaluation of the PillCam Colon capsule in the detection of colonic pathology: results of the first multicenter, prospective, comparative study - Eliakim, R; Fireman, Z; Gralnek, I M; Yassin, K; Waterman, M; Kopelman, Y; Lachter, J; Koslowsky, B; Adler, S N (Endoscopy, 2006)
Population-based screening for colorectal cancer is widely recommended, with conventional colonoscopy considered to be the preferred diagnostic modality. However, compliance with screening colonoscopy is low and manpower capacity is limited. Capsule endoscopy might therefore represent a desirable alternative strategy. The PillCam Colon capsule endoscope was prospectively tested in a multicenter setting. The indications for endoscopy in the enrolled patients included colorectal cancer screening (43 %), postpolypectomy surveillance (26 %), and lower gastrointestinal signs and symptoms (31 %). Study subjects underwent colon preparation and then ingested the capsule on the morning of the examination, with conventional colonoscopy being performed the same day. The PillCam Colon capsule findings were reviewed by three experts in capsule endoscopy who were blinded to the conventional colonoscopy findings. A total of 91 subjects were enrolled in three Israeli centers (55 men, 36 women; mean age 57), and the results were evaluable in 84 cases. The capsule was excreted within 10 hours in 74 % of the patients and reached the rectosigmoid colon in the other 16 %. Of the 84 evaluable patients, 20 (24 %) had significant findings, defined as at least one polyp of 6 mm or more in size or three or more polyps of any size: 14/20 (70 %) were identified with the capsule and 16/20 (80 %) were identified by conventional colonoscopy. Polyps of any size were found in 45 patients, 34/45 (76 %) found by the capsule and 36/45 (80 %) by conventional colonoscopy. In comparison with conventional colonoscopy, false-positive findings on PillCam Colon capsule examination were recorded in 15/45 cases (33 %). There were no adverse events related to the capsule endoscopy. PillCam Colon capsule endoscopy appears to be a promising new modality for colonic evaluation. Further improvements in the procedure will probably increase capsule examination completion and polyp detection rates. Additional studies are needed to evaluate the accuracy of PillCam Colon endoscopy in other patient populations with different prevalence levels of colonic disease.